Effect of rice husk ash and cattle manure on sweet corn in peat soil - Nadhira Ghea Salsabila; Dedik Budianta; Naomi Tias Brilian; Warsito (Jurnal Ilmu Tanah dan Air, 2026)
Sweet corn (Zea mays L. saccharata) productivity on peat soils is often constrained by high acidity, low fertility, and limited nutrient availability. Organic-based soil amendments such as rice husk ash and cattle manure may improve soil chemical properties and support crop growth on peatlands. This study aimed to evaluate the effects of rice husk ash and cattle manure on the growth and yield of sweet corn cultivated on peat soil. The field experiment was conducted from December 2022 to February 2023 at Bandar Agung Village, Lalan District, Musi Banyuasin Regency, while laboratory analyses and data processing were completed from June 2022 to May 2023. The study used a factorial randomized block design with two factors and three replications. Rice husk ash was applied at rates of 0, 30, and 60 t ha⁻¹, while cattle manure was applied at 0, 42, and 84 t ha⁻¹. The results showed that treatment A2S1 (60 t ha⁻¹ rice husk ash and 42 t ha⁻¹ cattle manure) tended to produce higher values for several yield parameters, particularly cob length, cob weight, and cob diameter. The treatments significantly affected cob diameter, number of leaves, cob length, and cob weight with husk and without husk, whereas plant height, plant wet weight, and plant dry weight were not significantly affected. The application of rice husk ash, cattle manure, and dolomite also increased soil pH under acidic peat soil conditions. These findings indicate that appropriate combinations of organic amendments may improve sweet corn productivity and support sustainable peatland agriculture.